(untitled) (Journal of the College of Basic Education, 2022)
In this paper, we will study a modified Integro-Differential Equations Of Fractional Order of the form : where the fractional order of differentiation and integration are different from each other, in which the Adomain decomposition method have been used to solve such type of problems for linear and non linear and cases, where such type of problems are so difficult to solve using other methods. Introduction :